The splicing factor SR2 is an important virulence factor of Toxoplasma gondii - Wu, Xiao-Jing; Gao, Jin; Zheng, Xiao-Nan; Elsheikha, Hany M.; Li, Ting-Ting; Kou, Yong-Jie; Wang, Meng; Zhu, Xing-Quan (Frontiers in Microbiology, 2023)
Serine/arginine-rich (SR) proteins are key factors with important roles in constitutive and alternative splicing (AS) of pre-mRNAs. However, the role of SR splicing factors in the pathogenicity of T. gondii remains largely unexplored. Here, we investigated the role of splicing factor SR2, a homolog of Plasmodium falciparum SR1, in the pathogenicity of T. gondii. We functionally characterized the predicted SR2 in T. gondii by gene knockout and studied its subcellular localization by endogenous protein HA tagging using CRISPR-Cas9 gene editing. The results showed that SR2 was localized in the nucleus and expressed in the tachyzoite and bradyzoite stages. In vitro studies including plaque formation, invasion, intracellular replication, egress and bradyzoite differentiation assays showed that deletion of SR2 in type I RH strain and type II Pru strains had no significant effect on the parasite growth and bradyzoite differentiation (P > 0.05). Interestingly, the disruption of SR2 in RH type I (P < 0.0001) and Pru type II (P < 0.05) strains resulted in varying degrees of attenuated virulence. In addition, disruption of SR2 in type II Pru strain significantly reduced brain cyst burden by ~80% (P < 0.0001). Collectively, these results suggest that splicing factor SR2 is important for the pathogenicity of T. gondii, providing a new target for the control and treatment of toxoplasmosis.